2014
DOI: 10.1111/jog.12532
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following different surgical approaches of myomectomy

Abstract: LM is a feasible treatment for women who have fertility requirements but suffer from leiomyoma. Although LM does not increase the rate of uterine rupture in the subsequent pregnancy, it is advisable for surgeons to limit the use of electrosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 34 publications
2
36
0
2
Order By: Relevance
“…In terms of safety during pregnancy, we found that the incidence rate of pregnancy complications was 10.8%, similar to that of myomectomy (6.8–13%) 19, 20, 44, 47, 48 . The most common complications of pregnancy in this study were placenta previa and placenta implantation.…”
Section: Discussionsupporting
confidence: 69%
“…In terms of safety during pregnancy, we found that the incidence rate of pregnancy complications was 10.8%, similar to that of myomectomy (6.8–13%) 19, 20, 44, 47, 48 . The most common complications of pregnancy in this study were placenta previa and placenta implantation.…”
Section: Discussionsupporting
confidence: 69%
“…[12] Furthermore, the pregnancy rate was significantly higher in the TAM group than that in the LM group, although there was no significant difference between these two types of surgical approach in terms of myoma number, myoma size, age, and whether the uterine cavity was distorted or not. The reason for why the TAM group resulted in a higher pregnancy rate remains unclear, although this might be attributable to the slightly larger myoma diameter in this group of women (7 [5.3–8.0] cm, 6 [5.0–7.0] cm, P = 0.050) in the TAM group.…”
Section: Discussionmentioning
confidence: 99%
“…However, if thermal denaturation and necrosis affect the surrounding tissues, unexpected complications such as weakening of tissues, formation of dead spaces, thinning of the muscle layer, and scarring can occur. [7][8][9][10]16,17,19,22) These complications can also adversely affect subsequent pregnancies. Because uterine rupture occurred in 3 women who had been treated for pedunculated subserous myoma using resection, coagulation, and hemostasis with an electrocauterizer and one woman with endometriosis in the posterior uterine wall, which had only been cauterized with an electrocauterizer, even application of coagulation and hemostasis processes to the uterine surface can apparently produce thermal denaturation and necrosis deep in the muscle layer.…”
Section: Precautions For Uterine Myomectomy and Technical Training Prmentioning
confidence: 99%
“…However, if thermal denaturation and necrosis affect the surrounding tissues, unexpected complications, such as weakening of tissues, formation of dead spaces, and thinning of the muscle layer, may occur. [7][8][9][10] These complications may adversely impact subsequent pregnancies. Surgeons often receive feedback regarding the short-term outcomes and complications of surgery.…”
Section: Introductionmentioning
confidence: 99%